Critical limits for the control points for halal poultry slaughter - Shahdan, Intan Azura; Regenstein, Joe Mac; Rahman, Mohammad Tariqur (Oxford University Press, 2016)
This study proposes critical limits (CL) for control points for halal slaughter (CPHS). Previously, 6 control points (CP) were determined, and CL for these 6 CPHS are suggested based on: 1) a literature survey for the CL for CP 1 (poultry breeding, rearing, and poultry feed) and CP 2 (welfare of poultry during transportation and lairage); 2) a field survey of slaughter plants in Kuantan (Malaysia) for CP 3 (immobilization), CP 4 (slaughter), CP 5 (time for full bleed-out), and CP 6 (washing and packaging); and 3) controlled experiments to refine the CL for CP 3, 4, and 5. The CL for CP 1 focused on stress reduction during rearing and use of substances that could compromise poultry meat wholesomeness. The CL for CP 2 emphasizes humane best-practices for handling poultry during lairage. The CL for CP 3 suggests a gap of 5 s between 2 shackles if only one shackler is employed and shackling times of <1 min for live chickens. In countries permitting water-bath electrical stunning of halal poultry, the stunning current needed to induce unconsciousness must be defined for the breed and bird size but not cause any chicken deaths. The CL for CP 4 mandates the recitation of the tasmiyah (the invocation), which if done for every chicken, will require ≥5 s between stunning and neck cutting. The CL for CP 4 also includes information about the slaughter knife. In CP 5 the recommended minimum time between neck cutting and scalding is 9.5 min. Finally, the CL for CP 6 emphasizes good supply chain hygiene and zero adulteration from haram species and substances.